"Living in the Darkness": Technology-Facilitated Coercive Control, Disenfranchised Grief, and Institutional Betrayal. (April 2023) - Woodlock, Delanie; Salter, Michael; Dragiewicz, Molly; Harris, Bridget
This article draws on interviews with 20 Australian women subjected to technology-facilitated coercive control (TFCC), foregrounding their accounts of grief and institutional betrayal. Findings show that while the harms of TFCC were significant, survivors' experiences were often minimized and dismissed by justice institutions. Women experienced grief due to abuse and separation from partners who had betrayed them. This loss was compounded when seeking help. We propose that disenfranchised grief is an underexplored response to domestic violence and institutional betrayal as well as a potential intervention site, particularly in relation to technology-facilitated abuse.